Granger causality : exchange rate and macroeconomic variables movements in Singapore / Hazwani Haziyah Mohd Ali - Mohd Ali, Hazwani Haziyah (Faculty of Business and Management, 2016)
The purpose of this study is to analyze the direction of causation between exchange rate and selected macroeconomics variables. In order to assess whether there is any potential impact between the variables, a Granger-causality analysis has been carried out to test the impact. It is to clarify how this variable factors and exchange rate movement impact each other.